2022
DOI: 10.1002/jmv.28036
|View full text |Cite
|
Sign up to set email alerts
|

Genomic annotation and molecular evolution of monkeypox virus outbreak in 2022

Abstract: Monkeypox virus (MPXV) has generally circulated in West and Central Africa since its emergence. Recently, sporadic MPXV infections in several nonendemic countries have attracted widespread attention. Here, we conducted a systematic analysis of the recent outbreak of MPXV‐2022, including its genomic annotation and molecular evolution. The phylogenetic analysis indicated that the MPXV‐2022 strains belong to the same lineage of the MPXV strain isolated in 2018. However, compared with the MPXV strain in 2018, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
147
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 17 publications
12
147
1
2
Order By: Relevance
“…Primers and probe sequences used in the MPV_F3L assay showed >99.4% alignment against the genome database, suggesting its suitability for detection of the MPV-2022 outbreak. Primers used in the MPV_G2R assay designed to detect the West African strain showed a 100% match to the database and 95.6% match for the probe thereby validating previous phylogenetic analysis results that the current MPV lineage belongs to the West Africa clade (20).…”
Section: Resultssupporting
confidence: 79%
“…Primers and probe sequences used in the MPV_F3L assay showed >99.4% alignment against the genome database, suggesting its suitability for detection of the MPV-2022 outbreak. Primers used in the MPV_G2R assay designed to detect the West African strain showed a 100% match to the database and 95.6% match for the probe thereby validating previous phylogenetic analysis results that the current MPV lineage belongs to the West Africa clade (20).…”
Section: Resultssupporting
confidence: 79%
“…The emergence of this outbreak is regarded as a global threat, and the World Health Organization declared a Public Health Emergency of International Concern on 23 July 2022 [ 1 ]. Since the elimination of the smallpox virus in 1980, MPXV has been considered the most severe orthopoxvirus circulating in humans as an incidental host [ 2 ]. As of 27 July 2022, 20,638 cases have been identified in 77 countries worldwide, 71 of which had never reported an MPXV infection before this outbreak [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MPXV involved in the 2022 outbreak belongs to Clade 3, lineage B.1 [ 20 ]. Although this double-stranded DNA virus shows a low mutation frequency, a comparison with the strains isolated in 2018 has revealed 46 common mutations among the strains involved in the 2022 outbreak [ 2 , 21 ]. An in-depth mutational analysis also suggested a potential MPXV human adaptation during the ongoing microevolution [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In France, the first draft genome was released on 25/05/2022 in Southwest France (Croville et al, 2022). Phylogenomic studies of MPX viruses involved in this 2022 outbreak indicated that these viruses belong to clade 3 and likely have a single origin (Isidro et al, 2022b;Wang et al, 2022;Jones et al, 2022). They further indicated that these viruses comprise a lineage named B.1 that derives from the A.1 lineage whose members were associated with the large outbreak in 2017-2018 in Nigeria and with MPX virus exportation from Nigeria to the United Kingdom, Israel and Singapore in 2018-2019 (Mauldin et al, 2022;Isidro et al, 2022b).…”
mentioning
confidence: 98%
“…The copyright holder for this preprint this version posted September 26, 2022. ; https://doi.org/10.1101/2022.09.26.509493 doi: bioRxiv preprint experts-give-virus-variants-new-names)) linked to outbreaks in Democratic Republic of Congo, clade 2 (or WHO clade IIa) linked to West Africa, and clade 3 (or WHO clade IIb) that encompasses viruses originating from the 2017-2018 outbreak that began in Nigeria and now those involved in the current 2022 multicountry outbreak (Berthet et al, 2021;Isidro et al, 2022b, Luna et al, 2022Mauldin et al, 2022;Wang et al, 2022). Although human MPX virus infections imported from subSaharan Africa have occurred in non-endemic countries (Mauldin et al, 2022), they only caused sporadic cases or very limited outbreaks until 2022.…”
mentioning
confidence: 99%